Practising the utopia. Edward Abramowski and the returning spectre of communism - Piskała, Kamil (Hybris, 2014)
The article discusses the idea of the communism comprised in the works of Polish radical thinker, Edward Abramowski (1868–1918). The Abramowski's works are examined in a strictly political manner. The article argues, that Abramowski's concept of the communism was created in the opposition to orthodoxical marxism, dominant in European workers movement that time. Abramowski was a determined critic of separating the „theory” and „practice” in workers movement program. The article proposes term „utopian practice” to analyse Abramowski's concept of the political activity and his way of thinking about class struggle and abolition of the capitalism, which – according to Abramowski – should be replaced by the „Cooperative Republic” (Republika Kooperatywna) – pre-communist utopia based on workers free associations. The article points out similarity (based on the concept of the „onologisation of the politics”) between Abramowski's concept of „everyday communism” and theories of Michael Hardt and Antonio Negri.